Challenges, Inquiry, and Recommendations: Effective COVID-19 Vaccine Management in the Face of Public Mistrust and Concern - Caron, Rosemary M.; Dorsey, M. Girard (Frontiers in Communication, 2022)
By examining concerns about safety, compliance, and distribution through an interdisciplinary approach of public health and history, we argue that historical and contemporary mistrust of immunizations serves to challenge the successful management of a COVID-19 vaccine program in the U.S. Unique circumstances surrounding the development of a COVID-19 vaccine, including pressure for rapid production, unclear communication from public health officials, and existing resistance to behavioral protective public policy measures (e.g., mask wearing) might complicate widespread vaccine adoption. Overall, a vaccine may evoke public resistance by confronting lay behavior, public expectations, and individual rights. To support the successful management of a vaccine program, we recommend public health education and communication measures that can be tailored to local community needs while preparing realistic public expectations surrounding the efficacy of a COVID-19 vaccine. A tailored approach holds the potential to dissuade vaccine hesitancy in American society. As COVID-19 variants are progressing, and the number of first COVID-19 vaccine doses continues to decline at this time in the U.S. population, and the demand for second doses in the U.S. wanes thus indicating a stalled vaccination program, the probability of not reaching herd immunity is quite likely. The perspectives offered herein present a pathway that is applicable to the current COVID-19 vaccine management program in the U.S., other global locations, and future pandemics.